ANALISIS PERILAKU KONSUMEN DALAM BERBELANJA PADA ZAN MART DI KABUPATEN BENGKULU SELATAN - Siti Hanila; Nia Indriasari (UNIVED Press, 2018)
Siti Hanila, Nia Indriasari; The purpose of this study is to determine the factors of completeness of products and services have an effect on buying decision in shopping at Zan Mart in South Bengkulu Regency. The population in this study is all consumers who happened to visit and buy in Zan Mart. Sampling using random sampling technique that amounted to 100 people. From the calculation results simultaneously obtained Fcount of 48.499 while Ftable 3.09 Ho thus rejected and Ha accepted simultaneous means of completeness of products and services have a significant effect on buying decision at Zan Mart in South Bengkulu Regency. Partially obtained by tcount X1 = 13,9481 and tcount X2 = 7,8455 and ttable 1,98 means Ho is rejected, so partially completeness of product and service have significant effect to buying decision. The conclusion of the research results that there is influence of completeness of products and services to the decision to buy at Zan Mart in South Bengkulu Regency. Effect simultaneously equal to 51,2% and partially influence of variable X1 = 66,5% and variable X2 = 38,6%. Suggestions that can be given is the Zan Mart should pay attention to the completeness of the product and offered so that consumers will feel satisfied. Regarding the service, should be more attention especially the element of speed, accuracy, security, friendliness, and comfort because service variables have a big enough influence in the decision to buy on Zan MartKey Words: Completeness Of Product, Service And Buying Decision.